2016
DOI: 10.1038/srep20609
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric obstructive sleep apnoea syndrome (OSAS) is associated with tonsil colonisation by Streptococcus pyogenes

Abstract: The involvement of pathogenic bacteria in obstructive sleep apnoea syndrome (OSAS) has yet to be elucidated. We investigated the possible role of group A streptococcus (GAS) in OSAS pathogenesis. In 40 tonsillectomized patients affected by OSAS and 80 healthy controls, significant (p < 0.0001) association of GAS with paediatric OSAS was found. Supernatant from streptolysin O (SLO)-producing GAS induced production of cysteinyl leukotrienes (CysLTs) in tonsil mononuclear cells (TMCs). CysLTs-treated TMCs showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 52 publications
(87 reference statements)
1
26
0
Order By: Relevance
“…8 The composition of immune cells in tonsils from recurrent GAS tonsillitis patients and from tonsillar hypertrophy patients is similar, and upon stimulation with GAS, both produce a Th1 cytokine response. 136,147 A study by Viciani et al 177 reported an association between OSAS and GAS tonsil colonization. These authors showed that the GAS toxin SLO induced production of CysLTs by a TLR4-mediated pathway that involved the TLR adaptors MyD88 and Toll/IL-1R domain-containing adapter-inducing IFN-and p38 MAPK.…”
Section: Adenotonsillar Hypertrophy and Pediatric Sleep Apneamentioning
confidence: 99%
See 1 more Smart Citation
“…8 The composition of immune cells in tonsils from recurrent GAS tonsillitis patients and from tonsillar hypertrophy patients is similar, and upon stimulation with GAS, both produce a Th1 cytokine response. 136,147 A study by Viciani et al 177 reported an association between OSAS and GAS tonsil colonization. These authors showed that the GAS toxin SLO induced production of CysLTs by a TLR4-mediated pathway that involved the TLR adaptors MyD88 and Toll/IL-1R domain-containing adapter-inducing IFN-and p38 MAPK.…”
Section: Adenotonsillar Hypertrophy and Pediatric Sleep Apneamentioning
confidence: 99%
“…GAS pharyngitis is associated with pediatric adenotonsillar hypertrophy (abnormal enlargement of the tonsil) and has recently been implicated in pediatric OSAS, which is primarily characterized by enlarged tonsils. 177 Tonsillar hypertrophy is caused by the proliferation of immune cells in the follicles and interfollicular areas of the tonsils in response to infection, and GAS was present in the tonsillar-reticulated crypt epithelium of 37% of children who had tonsillectomy for adenotonsillar hypertrophy. 8 The composition of immune cells in tonsils from recurrent GAS tonsillitis patients and from tonsillar hypertrophy patients is similar, and upon stimulation with GAS, both produce a Th1 cytokine response.…”
Section: Adenotonsillar Hypertrophy and Pediatric Sleep Apneamentioning
confidence: 99%
“…reported an association between OSAS and GAS tonsil colonisation. These authors showed that the GAS toxin SLO induced production of CysLTs, by a TLR4-mediated pathway, that involved the TLR adaptors MyD88 and TRIF and the p38 MAP kinase (130). CysLTs activated primary T and B cell proliferation in vitro, which might mediate the development of tonsil hypertrophy, and thus paediatric OSAS.…”
Section: Adenotonsillar Hypertrophy and Paediatric Sleep Apnoeamentioning
confidence: 99%
“…GAS pharyngitis is associated with paediatric adenotonsillar hypertrophy (abnormal enlargement of the tonsil) and has recently been implicated in paediatric obstructive sleep apnoea syndrome (OSAS), which is primarily characterised by enlarged tonsils (130). Tonsillar hypertrophy is caused by the proliferation of immune cells in the follicles and interfollicular areas of the tonsils in response to infection, and GAS was present in the tonsillar reticulated crypt epithelium of 37 % of children who had tonsillectomy for adenotonsillar hypertrophy (48).…”
Section: Adenotonsillar Hypertrophy and Paediatric Sleep Apnoeamentioning
confidence: 99%
See 1 more Smart Citation